Bore Disruption: An Unusual Mechanical Failure of Two Hip Hemiarthroplasties - Dettoni, Federico; Cottino, Umberto; Spriano, Silvia; Bonasia, Davide Edoardo; Rossi, Roberto (Joints, 2017)
We report a case of two hemiarthroplasties (HAs) that underwent an unexpected mechanical failure. Two patients affected by femoral fractures were treated with an HA. At 5 and 7 years after surgery, they showed a breakage of the HA at the head–stem junction. We analyzed macroscopically and microscopically (by a scanning electron microscopy) the surfaces of the broken prostheses. In both cases, a fracture was detected starting at the joining point between the femoral head and the slot that receives the taper cone of the stem (the so-called bore), with the typical macroscopic and microscopic pattern of a fatigue fracture. The fatigue fracture resulted from repeated cycles of torsional stresses throughout the years. In literature, we did not find any other report of such HA failure.
Keywords: fatigue; fracture; hemiarthroplasty; hip; scanning electron microscopy